Synthesis, electrochemical, in-situ spectroelectrochemical and in-situ electrocolorimetric characterization of new phthalocyanines containing macrocyclic moieties - KOCA, ATIF (ELSEVIER SCI LTD, 2014)
In this work, we synthesized new phthalocyanine compounds containing optically active 1,1'-binaphthyl crown ethers units. The metal-free phthalocyanine (3) was synthesized by the cyclotetramerization of dinitrile derivative (2) in dry n-pentanol by a classical method. However, metal phthalocyanines complexes (4, 5, 6), were synthesized by the reaction of dinitrile derivative (2) in DMAE. The structure of the new compounds were characterized by using spectroscopic data and elemental analysis. Electrochemical properties of Co (II) and Zn (II) phthalocyanines were investigated by using cyclic voltammetry and differential pulse voltammetry techniques. They exhibited two reversible Pc ring-based one-electron reduction couples. The Co (II) and Zn (II) phthalocyanines gave very similar voltammetric responses with slight potential shift due to different metal center. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cyclotetramerization; Phthalonitrile; Chirality; Dicarbonitrile; Electrochemistry; Spectroelectrochemistry; MICROWAVE-ASSISTED SYNTHESIS; METAL-FREE PHTHALOCYANINE; FUNCTIONAL PHTHALOCYANINES; ION SENSOR; COBALT; METALLOPHTHALOCYANINES; LIGANDS; SUBSTITUENTS; AGGREGATION; RECOGNITION